Rhetoric and reality in early Christianities - Braun, Willi, 1954- (Studies in Christianity and Judaism, 2005)
One of the most pressing issues for scholars of religion concerns the role of persuasion in early Christianities and other religions in Greco-Roman antiquity. The essays in Rhetoric and Reality in Early Christianities explore questions about persuasion and its relationship to early Christianities. The contributors theorize about persuasion as the effect of verbal performances, such as argumentation in accordance with rules of rhetoric, or as a result of other types of performance: ritual, behavioural, or imagistic. They discuss the relationship between the verbal performance of rhetoric and o.